The safety/tolerability of opicapone when used early in Parkinson's disease patients with levodopa-induced motor fluctuations: A post-hoc analysis of BIPARK-I and II - Rocha, José-Francisco; Ebersbach, Georg; Lees, Andrew; Tolosa, Eduardo; Ferreira, Joaquim J.; Poewe, Werner; Rascol, Olivier; Stocchi, Fabrizio; Antonini, Angelo; Magalhães, Diogo; Gama, Helena; Soares-da-Silva, Patrício (Frontiers in Neurology, 2022)
Introduction Post-hoc analyses of the BIPARK-I and II trials previously demonstrated that opicapone (OPC) 50 mg was efficacious over the whole trajectory of motor fluctuation evolution in patients with Parkinson's disease (PD) and end-of-dose motor fluctuations, with enhanced efficacy in patients who were earlier vs. later in their disease course and levodopa treatment pathway. Complementary post-hoc analyses were performed to evaluate the safety/tolerability of OPC following the same pre-defined segmentation of the wide spectrum of duration of both PD and levodopa therapy, as well as of motor fluctuation history, in this patient population. Materials and methods Data from matching treatment arms in BIPARK-I and II were combined for the placebo (PLC) and OPC 50 mg groups and exploratory post-hoc analyses were performed to investigate the safety/tolerability of OPC 50 mg and PLC in 22 subgroups of patients who were in “earlier” vs. “later” stages of both their disease course (e.g., duration of PD <6 years vs. ≥6 years) and levodopa treatment pathway (e.g., levodopa treatment duration <4 vs. ≥4 years). Safety/tolerability assessments included evaluation of treatment-emergent adverse events (TEAEs). Results The Safety Set included 522 patients (PLC, n = 257; OPC 50 mg, n = 265). For OPC 50 mg, incidences of TEAEs, related TEAEs, related serious TEAEs, and related TEAEs leading to discontinuation were lower for patients in earlier vs. later stages of their disease course and levodopa treatment pathway in 86.4, 86.4, 63.6, and 68.2% of the 22 pairwise comparisons conducted, respectively (compared with 63.6, 77.3, 18.2, and 45.5%, respectively, in the 22 corresponding PLC comparisons). Conclusion OPC 50 mg was generally well-tolerated when used to treat patients with PD with end-of-dose fluctuations, with an even more favorable tolerability profile in patients who were earlier, as opposed to later, in their disease course and levodopa treatment pathway, further supporting its use as an early adjunct to levodopa in PD.